Nanopore extended field-effect transistor for selective single-molecule biosensing - Ren Ren (Nature Portfolio, 2017)
Efficient detection of single molecules is vital to many biosensing technologies, which require analytical platforms with high selectivity and sensitivity. Ren et al. combine a nanopore sensor and a field-effect transistor, whereby gate voltage mediates DNA and protein transport through the nanopore.